Energy potential of sugarcane bagasse: contributions to the diversification of the Brazilian energy matrix - Nepomuceno, Nayana de Almeida Santiago; Vasconcelos, Ana Karine Portela (Brazilian Journal of Production Engineering, 2025)
This study aimed to identify the benefits of using sugarcane bagasse in energy cogeneration. The research was conducted through a Systematic Literature Review, based on a previously defined protocol, which established the keywords "sugarcane bagasse" and "cogeneration," as well as inclusion and exclusion criteria. After screening, six articles were selected for detailed analysis using Start software. Economic and environmental benefits of cogeneration using sugarcane bagasse were identified, including the reuse of ash generated by burning bagasse for construction applications.